Influência da coleta seletiva na composição gravimétrica dos resíduos sólidos de diferentes bairros de Lavras - MG - Sadi Junior, Hafez Tadeu (2015)
Population growth, industrial development and accelerated urbanization have been contributing to the increase in the use of natural resources and, consequently, in the generation of household solid waste – HSW that, when not appropriately managed, cause issues of sanitary, environmental, social and economic order. This paper aimed at determining the gravimetric composition of household solid waste of neighborhoods São Vicente, Caminho das Águas and Dona Flor, in the municipality of Lavras, Minas Gerais, Brazil, where selective collection was in process of implementation, with the intent of aiding the Association of Recyclable Material Collectors of Lavras – ACAMAR. We also studied neighborhoods Flamboyants Condominium, Monte Líbano and Jardim Eldorado, also in Lavras, where selective collection has been implemented for a few years. In the three first neighborhoods, the characterization was done in October of 2013 and June of 2014 (before and after the implementation of selective collection) and, in the three last neighborhoods, the collection was done in June of 2014. The waste was collected in a dump truck, by an outsourced company hired by the city hall, in previously defined routes and taken to the municipal dumping ground where the quarters method and gravimetric characterization were performed. We applied a socio-economic questionnaire in the neighborhoods regarding waste disposal habits. Based on the data, we verified that the population must be made better informed/aware of solid waste, especially regarding the adequate form of separation, especially in neighborhoods in which selective collection was recently implemented. The amount of organic matter, materials passive of being recycled and of rejects follow the national tendency in terms of percentage. We also verified that, even in the neighborhoods in which selective collection occurs for years, there is a considerable percentage of materials passive of being recycled being sent to the municipal dumping ground. We conclude that household solid waste in the municipality of Lavras, according to the tendency of the evaluated neighborhoods, have the potential for the public authority and/or ACAMAR to implement a more extensive Selective Collection and Organic Matter Composting Program in the municipality.